Econometric Model of the Gross Domestic Product - Mišeikis, Feliksas; Zabulytė, Loreta (Ekonomika, 2003)
An econometric model is one of the tools that economists use to forecast future developments in the economy. In the simplest terms, econometricians measure past relationships between variables such as consumer spending and gross national product, and then try to forecast how changes in some variables will affect the future course of others.The main idea of the article is to make econometric model of the gross domestic product. First of all a theory of the gross domestic product by expenditure approach is described. Secondly, equations that describe consumption, investment and import are formed and estimated. It is very important to form the equations so that the fitted data correspond with the actual as much as it is possible. After that a model which corresponds with the data best is made. Finally, this model is used to forecast.